Optimal Hedging Policies for Hydropower Generation at Ubolratana Reservoir - Rittima, Areeya (Agriculture and Natural Resources, 2012)
Hydropower is regarded as an important source of electrical energy to enhance the efficiency of renewable energy use. However, the effects of the inflow uncertainty on a reservoir operation which cannot maintain the water level so that it is sufficient for generating power in some critical periods, makes reliable energy generation in certain periods unpredictable. Thus, this research developed different types of optimal hedging policies (one-point hedging, two-point hedging, three-point hedging, multiple hedging-non seasonal effects and multiple hedging-seasonal effects), which facilitate energy generation in association with basic operational concepts. The aim of the hedging policies was to reduce the water release in some periods even when there was enough water for serving all sectors of water demand. Consequently, the water level in the reservoir would be higher and this would be beneficial for energy generation. This research used the reservoir water balance concept to construct a reservoir operational model and applied the optimization approach with a genetic algorithm to find the optimal parameters of each policy. The Ubolratana Reservoir in Thailand was selected as the study area. The simulated results and their performance based on the reservoir operational model with the optimal hedging policies using daily long term data from 1970 to 2010 showed that using the various types of optimal hedging for the reservoir operation produced higher levels of firm energy. Moreover, the two types of multiple hedging gave better performance in terms of higher energy production compared to the existing rule curve. Additionally, using optimal multiple hedging with the seasonal parameters for operation increased energy production by controlling the reservoir water level so that it did not exceed the normal pool level and was not lower than the minimum pool level. In principle, when the optimal hedging policies were applied, the water storage in the reservoir was strictly limited and did not encroach the surcharge storage and inactive zones in some critical drawdown and fulfilled periods. Therefore, some water storage was kept in the active storage zone and was beneficial for energy generation together with other off-stream uses downstream.